The effect of voluntary head movements on postural kinetics in the standing cat - Song, Yang (PeerJ, 2019)
BACKGROUND: Although the postural instability accompanying bilateral vestibular loss in human and quadrupeds during lateral head movements are well-known, it is still unclear whether or not lateral head turns would indeed activate the postural control system to maintain balance. This study aimed to examine the kinetic parameters in freely standing intact cats during head movements in order to further answer the above question. METHODS: Six intact cats were trained to stand, unrestrained on a force plate and perform voluntary head movements to the left and right positions in response to visual cues. Each trial was divided into two phases, quiet standing with the cat’s head maintaining a straight forward and lateral head position after voluntary head movements. Kinetic parameters including peak pressure and contact area under each limb as well as center of pressure (COP) displacements of the whole body were measured. RESULTS: Compared to the neutral head position, peak pressure and contact area of the left head position were significantly smaller for the left forelimb while greatly larger for the right forelimb. An exact opposite case of peak pressure and contact area in the forelimbs was found between the right and neutral head positions. In addition, the COP displacements altered oppositely to the head movements, and presented a significantly right shift in the left position and a significantly left shift in the right position. CONCLUSION: These results demonstrate that the lateral displacement of the head in standing intact cats does activate the postural adjustment to maintain balance, which is consistent with the concept that vestibular input can contribute to postural balance during voluntary head turns.